Developmental & Autism Screening in Epilepsy Unit - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Epilepsy Center, Ann & Robert H Lurie Children's Hospital of Chicago assessed the yield of routine screening for neurodevelopmental delay and autism in all patients, 5 years of age and younger, seen in the monitoring unit or ketogenic diet clinic.